An analysis of the winning national science fair projects in chemistry - Alojipan, Dorinda Mancebo 1933-
This is an analysis of the winning entries in the National School Science Fair in the Chemistry category for the years 1972, 1973 and 1974. The results of the study revealed that most of the procedures used in the projects are suitable to the high school level except for a few procedures which require special equipment and special knowledge or training to perform the experiment.
Thesis (M.A.T.)--University of the Philippines, Quezon City.
Keywords: Science -- Exhibitions -- Philippines; Chemistry -- Experiments